PENGARUH MOTIF PUJIAN PELANGGAN TERHADAP KOMITMEN PELANGGAN - Lizar Alfansi; Ferry Tema Atmaja (The Manager Review, 2019)
The compliment given by customers is a valuable input for companies to improve performance in the future. Companies can minimize errors in service and increase customer satisfaction through policies to listen and respond positively to every complaint and compliment delivered by customers. The policy does not require a large investment, but the company only provides facilities and procedures that are not complicated for customers to deliver complaints or compliment to the company. Although research on compliment behavior has been carried out in developed countries, similar studies conducted by researchers in Indonesia are still limited. The results showthat customer compliment motives have an influence on commitment. This explains that the higher the level of motives of someone’s compliments, the higher the person's commitment to the company. Conversely, testing the hypothesis does not prove the relationship of motives of praise to commitment moderated by cultural factors and social factors.